REPRESENTASI PERFORMA BUDAYA PASSURA’ PADA MASYARAKAT TORAJA - Waliyuddin; Ansar, Nurhakki; Abdul Rasyid (Jurnal Dakwah Tabligh, 2024)
Passura' is a carving that is the identity of cultural performance in the Toraja people which has the characteristics of signs and conditions with meaning. Passura' is used not only for aesthetic purposes in Tongkonan houses and typical Toraja fashion and accessories but also has a meaning that is represented in the life of the Toraja people. This research with a descriptive qualitative method aims to describe the meaning and representation of meaning in the dimension of socio-cultural life, as well as the position of passura as a cultural performance in Toraja society. passura based on the perspective of its interpretation, the results of this study show that; (1) Passura' as a sign consists of shapes, colors, and types that have a complex phenomenon. The shape that becomes a sign is the shape of nature and flora and fauna, the color consists of black, white, yellow, and red, and the types are grouped in the level of passura'. Each sign represents something outside the object itself; (2) the representation of passura in Toraja life includes (a) the representation of the existence of strata and social roles or with Tana' known in Tana' Bulawan, Tana' Bassi, Tana' karurung, and Tana' Kua-kua; (b) as a representation of aluk or the rules of social life that must be carried out by all individuals and communally, because all the rules of aluk that are carried out are engraved in the form of passura'; (c) as a representation of the rules of the relationship between man and creator as well as man and nature in Toraja teachings is called aluk Tallu Lolona; (d) as a representation of the greatness, leadership, and welfare of the Toraja Community because passura describes the figure of leaders or influential figures in Toraja society; (e) Representation of the spirit of togetherness of the unity of 'karapasan'; (3) The use of Passura' as a Cultural Performance includes: (a) Passura' as a process that has undergone an evolution of types and forms because it is influenced by popular culture, economy, and tourism factors; (b) Passura is used as an awareness of identity and devotion to ancestors, (c) as a Rites of Passage because it is used in every formal event as symbolism, stories, and actions in the Tana Toraja community from time to time.